Neither Baseline nor Changes in Serum Triiodothyronine during Levothyroxine/Liothyronine Combination Therapy Predict a Positive Response to This Treatment Modality in Hypothyroid Patients with Persistent Symptoms. Issue 2 (19th April 2017) - Medici, Bjarke Borregaard; la Cour, Jeppe Lerche; Michaelsson, Luba Freja; Faber, Jens Oscar; Nygaard, Birte
Abstract : Background: Despite biochemical euthyroidism, some levothyroxine (L-T4 )-treated hypothyroid patients report persisting symptoms and some of these patients are tentatively treated with a combination of L-T4 and liothyronine (L-T3 ). Combination therapy and the appropriate choice of blood tests to monitor treatment are highly debated among specialists and patients. Aim: To evaluate whether measuring serum triiodothyronine (S-T3 ) at baseline or during combination therapy can be used as an indicator of a positive effect from L-T4 /L-T3 combination therapy. Materials and Methods: Observational retrospective study of patients ( n = 42) with persisting symptoms of hypothyroidism despite L-T4 therapy who had normal TSH levels and did not have any comorbidities that could explain their symptoms. All were then treated with L-T4 /L-T3 combination therapy at a dose ratio of 17/1 according to European Thyroid Association guidelines. Based on patient-reported outcome, they were divided into responders and nonresponders. Results: Five patients were lost to follow-up and thus excluded. At the 3-month follow-up, 11 were classified as nonresponders and 26 as responders. At 12 months these figures had changed to 13 (35%) and 24 (65%), respectively. When comparing responders versus nonresponders, no differences were seen at baseline or during follow-up in S-T3 and in free T3 estimates. Further, logistic regression showed no correlation between S-T3 and free T3 estimates and responder/nonresponder status. Conclusion: Our data indicate that serum T3 measurements are not suitable to predict which patient will benefit from L-T4 /L-T3 combination therapy, and treatment response cannot be followed by repeated T3 measurements either.